GIS for sustainable living in the riverine communities in edu local government area of Kwara State, Nigeria - Oriola, Emmanuel Okunlola; Chibuike, Cynthia Chinelo (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
The importance of information in contemporary time is an issue that cannot be handled with levity. It implies that information has become power that pivot and propel the wheels of development. In this vein, this pilot study attempts to provide adequate information for sustainable development of riverine communities of Edu Local Government Area of Kwara state, Nigeria. Edu Local Government area was divided into three pragmatic zones based on the administrative districts. In each of the districts, Geographical Information System analytical tool was used to harvest and treat the data for subsequent interpretation. The coordinates of various locations of interest were captured, contour and slope maps of the area were generated to finally produce risk map for the area. The results revealed three distinct risk zones; High, Moderate and low-risk areas. Three settlements fall into low-risk areas with elevations above 196m, two settlements located at between 110m and196m are within moderate risk zone and six settlements in High-risk area with elevations below 110m. This study concludes that the riverine communities in Edu LGA are prone to flood risk. The study recommends public enlightenment on how man interacts with the environment and the implications, the trend in climate and weather in relation to flood and its consequences; environmental education and Stakeholder’s forum should be organized as avenue for disseminating and educating the people for better and sustainable living in their various communities.